Central Venous Catheter-Associated Bloodstream Infections in Hemodialysis Patients: Another Patient Safety Bundle?. Issue 2 (1st April 2006) - Johnston, B Lynn; Conly, John M
Abstract : In a previous issue of The Canadian Journal of Infectious Diseases & Medical Microbiology, we reviewed the 'Safer Healthcare Now!' campaign's focus on reducing central venous catheter (CVC)-associated bloodstream infections (BSIs) as a way of improving patient safety (1). This initiative is focused on preventing CVC-associated BSIs in intensive care units. However, other patient groups are also at risk for CVC-related BSIs, suggesting that there are other individuals who would benefit from preventive efforts. A 1996 hospital-wide survey of nosocomial bacteremia in an Israeli university hospital (2) found that 9% of infected patients were on chronic hemodialysis. Surveillance in 73 hospitals in England between 1997 and 2001 found a CVC BSI rate of 21/1000 nephrology patients at risk who were hospitalized in teaching hospitals (3). This rate was similar to that found in special care neonatal units, although not quite one-half that of patients in a general intensive care unit. In a population-based survey performed in the Calgary Health Region from 2000 to 2002 (4), hemodialysis (HD) posed the greatest risk (RR 208.7; 95% CI 142.9 to 296.3) for acquiring severe BSI.